Bibliometric Analysis and Visualization of Harm Reduction in Malaysia Indexed in Scopus - Harits Dwi Wiratma; Yeyen Subandi; Diansari Sholihah Amini; Tanti Nurgiyanti; Bagus Subekti Nuswatoro; Ananda Dewin Ikhtiarin; Seftina Kuswardhini; M Syamsurrijal (Universitas Respati Yogyakarta, 2022)
T Introduction: This study aims to analyze the bibliometric characteristics and trends of articles on Harm Reduction in Malaysia, indexed by Scopus. Methods: Data taken from the Scopus database, articles searched in August 2021 with restrictions on Harm Reduction affiliation in Malaysia. The keywords used in this research are Harm Reduction and Malaysia. Simple statistical methods were used, and bibliometric analysis was performed using VOSviewer software. This study visualizes the patterns of keyword co-occurrence, document citations, co-citation relationships, and bibliographic coupling. Results: The number of study articles in the field of Harm Reduction has not increased significantly in recent years; articles on Harm Reduction have been published in 67 journals with 76 documents from 1995 to 2021. Conclusion: Research on Harm Reduction in Malaysia has not been of much interest, and in the last five years, there has been no significant increase. Therefore, the findings in this study can provide valuable data for future researchers to understand research trends and find research novelties in Harm Reduction in Malaysia.